STUDIES ON GENETIC VARIABILITY, HERITABILITY AND GENETIC ADVANCE FOR YIELD, YIELD COMPONENTS AND QUALITY TRAITS IN PEANUT STEM NECROSIS TOLERANT GROUNDNUT GENOTYPES (Arachis hypogaea L.) - P. DHARANI NIVEDITHA, M. SUDHARANI, A. PRASANNA RAJESH; P.J. NIRMALA (The Journal of Research ANGRAU, 2015)
Fifty genotypes of groundnut were evaluated for their genetic variability, heritability and genetic advance for a set of 15 characters during kharif, 2015. Analysis of variance revealed the presence of highly significant differences among the genotypes for all characters indicating sufficient variability in the material studied. High PCV and GCV were observed for kernel yield plant-1, pod yield plant-1 and haulm yield plant-1. High heritability was observed for SPAD Chlorophyll Meter Reading at 60 days after sowing, protein content, plant height, kernel yield per plant, pod yield per plant and 100 kernel weight. High genetic advance as % of mean was observed for kernel yield, pod yield, haulm yield and protein content indicating that these traits were mainly governed by additive gene effects and response to selection could be affected for further improvement of pod yield through simple selection.